Systematic review in relation to support of diversity in nursing homes - Mesas-Fernández, Javier; Tous-Pallarès, Jordi; Espinoza-Díaz, Ivette Margarita (Frontiers in Aging, 2024)
IntroductionGiven the increasing global population of older adults, it is essential and inevitable that healthcare centers and nursing homes address and accommodate diversity in their support systems as interventions for healthy aging. The active aging and the inclusion of all people regardless of their religion, origin, and/or sexual orientation is essential to create a climate of safety. Discrimination must be addressed from all angles, at the social level, at the business level and by all workers in nursing homes.Methodology and resultsThis study provides a comprehensive review of existing literature to systematize information on diversity among older adults in healthcare centers and nursing homes. Out of 1.458 articles identified, 10 were analyzed in depth, revealing that addressing diversity among older adults is crucial to overall mental and physical healthy aging. The findings underscore the need for a multidisciplinary approach and effective management through the Person-Centered Care Model (PCCM).Discussion and conclusionThis study highlights the critical role of the Person-Centered Care Model (PCCM) in addressing diversity in aging needs. It highlights the necessity of tailoring care based on individual life histories and experiences. Additionally, it calls for the implementation of inclusive policies in nursing homes and emphasizes the need for professional training on diversity to ensure these facilities are safe and supportive for all residents.